FILMED SCENES IN TEACHING ENGLISH FOR NURSING TO IMPROVE THE COMMUNICATION AND MEDICAL SKILL - Amalia Rahmawati (Universitas Muhammadiyah Semarang, 2015)
ASEAN Economic Community (AEC) becomes the current issue in education field especially for nursing academy. The students should have good capability not only in medical aspects but also communication aspects. Speaking English is the key to have a good communication if AEC is realized. Therefore, lecturer should prepare the students to face AEC by applying new technique in teaching and learning process. This study aims to answer “is the use of Filmed Scenes in teaching English for nursing effective to improve the communication and medical skill?”. This study belongs to experimental study with posttest and observation as the data collection. This research was conducted in the even semester 2015. There were 82 students of second semester undergraduate nursing science program STIKES Muhammadiyah Kudus. The finding of this research shows that (1) the use of filmed scenes can improve the students’ vocabulary, communication skill and medical skill, (2) the use of filmed scenes can help the students to have realistic medical treatment, (3) the use of filmed scenes introduces the students to have interactive and communication therapeutic. This research recommended to explore and compare various methods in other subjects to achieve students, competence and develop quality nursing education.Key words: Filmed Scenes, Teaching English for Nursing, Communication Skill, Medical Skill